Additive Manufacturing Technology in the Furniture Industry: Future Outlook for Developing Countries - Tuazon, Brian J.; Dizon, John Ryan Cortez (Advance Sustainable Science Engineering and Technology, 2024)
For the past few years, the adoption of 3D printing technology has benefited various manufacturing industries, including the furniture making industry. However, this adoption has been greatly seen in industrialized countries and lacking in developing countries. Therefore, to understand fully the capability of 3D printing and its benefits, this paper review discusses recent applications of 3D printing in the furniture industry and assesses the potential it can bring for developing countries’ furniture making industry, specifically in the Philippines and other developing countries in Asia. In addition, the drawbacks it brought to the industry, and the challenges that needed to be addressed are also discussed in the paper. The paper covers various 3D printing technologies such as material extrusion, sheet lamination, powder bed fusion, and vat photopolymerization, along with different materials currently used in the furniture industry. Numerous notable examples of applications of 3D-printed furniture are also presented. Based on the review paper, it was found that the most common 3D printing technologies used in the furniture industry are Material Extrusion (MEX) and Powder Bed Fusion (PBF) specifically Fused Deposition Modelling (FDM) and Selective Laser Sintering (SLS), respectively. The most common 3D printing materials used are Polyamide (PA), Polylactic acid (PLA), and recycled Polyethylene terephthalate glycol (PETG). The paper also discusses the possible adoption of 3D printing in developing countries and explores its potential to innovate traditional furniture manufacturing processes.